Host Serine Proteases TMPRSS2 and TMPRSS11D Mediate Proteolytic Activation and Trypsin-Independent Infection in Group A Rotaviruses - Sasaki, Michihito; Itakura, Yukari; Kishimoto, Mai; Tabata, Koshiro; Uemura, Kentaro; Ito, Naoto; Sugiyama, Makoto; Wastika, Christida E.; Orba, Yasuko; Sawa, Hirofumi (Journal of virology, 2021)
Proteolytic cleavage of the viral VP4 protein is essential for virion maturation and infectivity in group A rotaviruses (RVAs). In cell culture, RVAs are propagated in culture medium supplemented with the exogenous protease trypsin, which cleaves VP4 and induces the maturation of progeny RVA virions. Group A rotaviruses (RVAs) are representative enteric virus species and major causes of diarrhea in humans and animals. The RVA virion is a triple-layered particle, and the outermost layer consists of the glycoprotein VP7 and spike protein VP4. To increase the infectivity of RVA, VP4 is proteolytically cleaved into VP5* and VP8* subunits by trypsin; these subunits form a rigid spike structure on the virion surface. In this study, we investigated the growth of RVAs in cells transduced with type II transmembrane serine proteases (TTSPs), which cleave fusion proteins and promote infection by respiratory viruses, such as influenza viruses, paramyxoviruses, and coronaviruses. We identified TMPRSS2 and TMPRSS11D as host TTSPs that mediate trypsin-independent and multicycle infection by human and animal RVA strains. In vitro cleavage assays revealed that recombinant TMPRSS11D cleaved RVA VP4. We also found that TMPRSS2 and TMPRSS11D promote the infectious entry of immature RVA virions, but they could not activate nascent progeny virions in the late phase of infection. This observation differed from the TTSP-mediated activation process of paramyxoviruses, revealing the existence of virus species-specific activation processes in TTSPs. Our study provides new insights into the interaction between RVAs and host factors, and TTSP-transduced cells offer potential advantages for RVA research and development. IMPORTANCE Proteolytic cleavage of the viral VP4 protein is essential for virion maturation and infectivity in group A rotaviruses (RVAs). In cell culture, RVAs are propagated in culture medium supplemented with the exogenous protease trypsin, which cleaves VP4 and induces the maturation of progeny RVA virions. In this study, we demonstrated that the host proteases TMPRSS2 and TMPRSS11D mediate the trypsin-independent infection and growth of RVAs. Our data revealed that the proteolytic activation of RVAs by TMPRSS2 and TMPRSS11D occurs at the viral entry step. Because TMPRSS2 and TMPRSS11D gene expression induced similar or higher levels of RVA growth as trypsin-supplemented culture, this approach offers potential advantages for RVA research and development.